Percursos estudantis de mobilidade acadêmica internacional: um estudo exploratório sobre experiências dos estudantes do Instituto Federal de Alagoas - Andrade, Carla Cristina Real Vieira de (2021)
This dissertation aims to analyze the student pathways of international academic mobility of seven students at the Federal Institute of Alagoas (Ifal) evidencing their experiences abroad, in order to verify the acquisition of a symbolic capital, the cultural/knowledge capital. The internationalization process is increasingly evident in higher education. In the Federal Institutes, although much has been advanced, it is a gap that lacks work to strengthen and expand teaching, research, extension and innovation activities that go beyond geographic and linguistic borders, through different ways of internationalizing. Given the context of globalization, it is necessary to understand the challenges that permeate this process through public policies that enable relationship initiatives with foreign institutions, increasing visibility and competitiveness in the field of vocational, technological, public and quality education. Thus, in analyzing the trajectory of these students, it is intended to understand the desire to study abroad, the challenges faced before, during and after the trip. In addition, realize the personal, vocational and academic gains that these students bring when they return to the country. When it comes to an international academic mobility deliberated by the educational institution, it is necessary to take into account the sharing of experiences brought by students so that the benefits are not only personal, but institutional, favoring everyone who makes up Ifal. The methodology of this work uses the case study method, with a qualitative approach in an exploratory research carried out through the interview technique with semi-structured questions. The analysis of the collected data is structured in five dimensions, namely: Welcoming/cultural adaptation, Teaching, Mobility's negative points, Mobility's positive points and Global Citizenship. These dimensions, achieved through the interviewees' answers, made it possible to respond to the objectives of this dissertation, identifying the reasons why students want to undertake international academic mobility, despite the various difficulties faced, with a view to exchanging experiences and knowledge about the globalization of labor market, as well as the expansion of the capacity to understand cultural diversity.